Communication, Resources, and Dispositional of Implementation Minister of Health Regulations - Pudentiana Rr. R. E.; Ita Astit Karmawati; Ita Yulita; Eka A. (Global Writing Academica Researching & Publishing, 2022)
From the perspective of George C. Edward III's research in Policy Implementation Research, this study examines how the Permenkes (Factor Communications, Resources, and Disposition) and related theories are implemented from the perspective of a researcher. The Executive Officer of the Department of Dental Health in 18 polytechnics in Indonesia was interviewed using primary data in a cross-sectional descriptive study. The Head of the Department/KAJUR and the Secretary of the Department/JKG were present for each data gathering. Sample data is collected using a nonprobability sampling approach. SPSS version 17 Complex Sample was used to analyze the data. Chi-square and multiple linear regression are used to analyze the data. The statistical tests revealed that none of the factors gathered throughout the communication process had a statistically significant relationship with the implementation. 1192/MENKES/PER/X/2004 is also a consideration in terms of resources and disposition. Lester and Stewart Jr. say that implementation is both a process and a result (output). Regardless of whether or not the aims are reached, the implementation of a policy can be judged or observed by the process and its outcomes (results). This is not dissimilar to what Merrile Grindle expresses. In addition, the results of the correlation test show that the three independent variables have a strong link and a favorable pattern of interaction. Communication requires gaining essential resources, creating strong relationships, and discovering positive patterned variables that have the disposition of a stand/disposition correctly, and it will increasingly be achieved through policy implementation.